2016
DOI: 10.3109/13561820.2015.1072142
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the importance of team psychological safety in the development of two interprofessional teams

Abstract: It has been previously demonstrated that interactions within interprofessional teams are characterised by effective communication, shared decision-making and knowledge sharing. This paper outlines aspects of an action research study examining the emergence of these characteristics within change management teams made up of nurses, general practitioners, physiotherapists, care assistants, a health and safety officer and a client at two residential care facilities for older people in Ireland. The theoretical conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 14 publications
2
34
0
Order By: Relevance
“…O'Leary [48] conducted action research meetings with two newly-formed interprofessional project teams. The supportive leadership style used by the author encouraged psychological safety within team meetings.…”
Section: Interventions Without Educational Componentmentioning
confidence: 99%
See 3 more Smart Citations
“…O'Leary [48] conducted action research meetings with two newly-formed interprofessional project teams. The supportive leadership style used by the author encouraged psychological safety within team meetings.…”
Section: Interventions Without Educational Componentmentioning
confidence: 99%
“…One further study [36] found no significant relationship. Three studies [39,46,47] reported improved and one study [48] found mixed results for "communication and collaboration" following interventions. Five studies [38,40,42,44,45] reported positive evaluations by participants postinterventions.…”
Section: Interventions Most Effective At Improving Psychological Safementioning
confidence: 99%
See 2 more Smart Citations
“…Establishing causal links in an inter-organisational context is even more complex than establishing them at individual and organisational level as it can be difficult to attribute outcomes to involvement in a network and to distinguish them from outcomes that may have occurred anyway (Provan and Sydow 2008). Complexity is also increased by the existence of various factors that can influence interactions between individuals from different backgrounds such as trust and power (O'Leary 2016). This can impact on network processes and outcomes and may also affect decisions on who should be involved in evaluation.…”
Section: How To Evaluate: Why Is It a Problem?mentioning
confidence: 99%